Illustration Design of Leang Leang Cave Tourist Attraction as an Icon in Animation Video Generative AI - Faizal Erlangga Makawi; Agussalim Djirong (Fakultas Sastra - Universitas Muslim Indonesia, 2026)
This study examined the use of illustration design as an icon in generative video animation using AI generative video to improve local attractiveness. The integration of technology on local tourism aims to improve the information to attract more visitors to Leang Leang Cave in Maros as an icon in international prehistoric cave. Leang Leang Maros provides many historical rock paintings that cannot be find in any part of the world. The Karst mountains provide many unsolved mysteries related to the age of the rock paintings. Thus, this study explores the potential of promoting Leang Leang Cave using AI generative video to create animation with strong illustration design. The method of this research is a qualitative research method, using the conceptual framework and four frames by Freeman (1995). The findings of this research demonstrated that the 19 respondents agreed that illustration is an effective visual representation. Because it provides original content, historical events, engaging visual presentations, and contemporary illustrations. The conceptual framework demonstrates that historical illustrations, identity, historical heritage, and strong story telling are key factors to improve the Generative AI video animation using Illustration design. While, in the four frames, originality, local wisdom, consistency, and contemporary interpretation are the key factors to improve. These categories are a fundamental key to promote for educational content and for media communication to attract tourism from around the world. The findings bring benefits not only for the visual communication design but also cultural heritage promotion in the Artificial Intelligence era.